If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 2(4x + -1) + -9 = 0 Reorder the terms: 3x + 2(-1 + 4x) + -9 = 0 3x + (-1 * 2 + 4x * 2) + -9 = 0 3x + (-2 + 8x) + -9 = 0 Reorder the terms: -2 + -9 + 3x + 8x = 0 Combine like terms: -2 + -9 = -11 -11 + 3x + 8x = 0 Combine like terms: 3x + 8x = 11x -11 + 11x = 0 Solving -11 + 11x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '11' to each side of the equation. -11 + 11 + 11x = 0 + 11 Combine like terms: -11 + 11 = 0 0 + 11x = 0 + 11 11x = 0 + 11 Combine like terms: 0 + 11 = 11 11x = 11 Divide each side by '11'. x = 1 Simplifying x = 1
| 5x-6=12x-7 | | 5p^2-2p=7 | | 24+y+3y=60 | | xx=144 | | 12(0.5*-5)=-6(-x+10) | | -1=5r | | 49x^2-69x+20=7x^2-8 | | 3y^2=15y | | 81x^2+4y^2=324 | | (X+18)+(x-20)=90 | | 4x+2x-1=5x | | 8x+28=3x+5 | | 6x^2-4x-5=0 | | 3x+1=2(2-x) | | t^2-t=20 | | 8x+28=2x+5 | | X-18+x-20=90 | | (x-2)-2(x+4)=3(2x-3) | | 5y^2-y+9=0 | | 180=15w | | y+2y+3y=24 | | 3x^2+7x-8= | | 3x+5=35-3x | | 180=w+15 | | 6x+18=9x | | (3x)+(x+20)+(2x+10)=90 | | 1-2(x+1)=4 | | 7n-6=4n-30 | | x^3-5x^2-24=0 | | 8x-3=4(2x+-3) | | (2y+7)(2y+7)=49 | | -(2z+2)+3(2z+4)-2z= |